National Resilience: Homeland Indonesia (Instilling the Character of Love for the Homeland in Elementary School/Islamic Elementary School Children) - Abdul Rahman; Meli Julianti; Ardina Khoirunnisa; Nurul Fadilah Nasution; M. Dzaky Labib Juhaidi (Yayasan Zia Salsabila, 2025)
The character of love for one's country is an attitude that every individual must have towards their nation and country. This character of love for one's country is also a positive value that needs to be instilled in students at school. Bearing in mind that currently many of the younger generation have begun to lose their sense of love for their country. Love for their country is a character that must be possessed by every citizen regarding the implementation of their rights and obligations and participating in efforts to defend the country. The aim of this research is to instill the character of love. homeland to children from an early age with the hope of creating a sense of pride, appreciation, respect and motivating themselves as adults to serve and be useful to the nation. This research uses qualitative research with literature study methods by collecting library data, reading, taking notes and discuss the material under discussion. The results of this research show that efforts to instill the character value of love for the homeland in elementary school children are through activities 1) Singing the National Song, 2) Flag ceremony activities, 3) Getting used to using good and correct Indonesian, 4) teaching material that supports love of the homeland , 5) Using domestic products.